Evaluating organ-specific radiation exposure in transcatheter arterial chemoembolization (TACE): A phantom-based assessment of safety thresholds for interventional radiology applications - Kayaokay, Duygu Tuncman; Ozgur, Eren; Kesmezacar, Fahrettin Fatih; Yeyin, Nami; Karacam, Songul Cavdar; Gunay, Osman; Demir, Mustafa; Tekin, H. O.; ALMisned, Ghada (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Objective: This study aims to evaluate radiation doses absorbed by critical organs during Transcatheter Arterial Chemoembolization (TACE) using Thermoluminescent Dosimeters (TLDs) placed within an Alderson Rando Phantom, and to assess these doses against established safety limits. Method: The Alderson Rando Phantom, known for its anatomical accuracy, was used to simulate radiation exposure during TACE procedures. TLDs were strategically positioned in the stomach, kidneys, liver, spleen, pancreas, vertebrae, and reproductive organs. The TLDs were calibrated with a Cs-137 gamma source, and measurements were taken using a Siemens Artis Zee C-arm system. Radiation doses were analyzed and compared to safety thresholds from clinical guidelines. Results: Our findings indicate that the average dose to critical organs remained within safe limits, with the liver receiving 32.75 +/- 0.065 mSv and kidneys 88.48 +/- 12 mSv. While doses for organs close to the target liver region were higher, all remained below tolerance thresholds. Conclusion: This study demonstrates that TACE can be performed safely with controlled radiation exposure to adjacent organs when proper protocols are followed. The Alderson Rando Phantom proved effective in simulating patient exposure, providing critical insights for enhancing radiation safety in interventional radiology.
Keywords: Transcatheter arterial chemoembolization; Radiation dosimetry; Alderson rando phantom; Radiation safety; Organ dose; NORMAL-TISSUE TOLERANCE; THERAPY; RISK; Chemistry; Nuclear Science & Technology; Physics